Write the expression (4x - 2) x 6(2x + 7) in the standard form of a quadratic expression, ax^2 + bx + c. What are the values of the coefficients of each term and the constant term: a = _________, b = __________, c = _________.

1 answer

To find the standard form of the quadratic expression, we need to multiply the given expression and simplify it.

First, distribute the 6 into the expression inside the parentheses:
(4x - 2) x 6(2x + 7)
= 6(4x - 2)(2x + 7)
= 6(8x^2 + 28x - 4x - 14)
= 48x^2 + 168x - 24x - 84
= 48x^2 + 144x - 84

Now, the standard form of a quadratic expression is ax^2 + bx + c, so in the given expression:
a = 48
b = 144
c = -84

Therefore, the values of the coefficients of each term and the constant term are:
a = 48, b = 144, c = -84